Effects of Machining Parameters on Abrasive Flow Machining of Single Crystal γ-TiAl Alloy Based on Molecular Dynamics - Junye Li; Chao Song; Xin Du; Hongcai Xie; Jinghe Zhao; Ying Chen (Micromachines)
Observing the intricate microstructure changes in abrasive flow machining with traditional experimental methods is difficult. Molecular dynamics simulations are used to look at the process of abrasive flow processing from a microscopic scale in this work. A molecular dynamics model for micro-cutting a single crystal γ-TiAl alloy with a rough surface in a fluid medium environment is constructed, which is more realistic. The evolution of material removal, cutting force, temperature, energy, and dislocation during micro-cutting are analyzed. The impact of cutting depth, abrasive particle sizes, and abrasive material on the micro-cutting process are analyzed. The analysis shows that the smaller cutting depth and abrasive particle sizes are beneficial to obtain a better machining surface, and the cubic boron nitride (CBN) abrasive is an effective substitute material for diamonds. The purpose of this study is to provide unique insights for improving the material removal rate and subsurface quality by adjusting machining parameters in actual abrasive flow precision machining.